SIGNIFICANCE OF MARKETING CAMPAIGNS FOR PROFESSIONAL SPORTS TEAMS - Shaurya Mehta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There are some variations in the understanding of the key categories and meanings with regard to the current popularity of the concept of sport marketing as a research, instructional and applicable discipline. Researchers and professionals, in fact, frequently distinguish between "sport marketing" and "sport marketing." The substance of the present differences resides in the reality that the concept of sport marketing and sport marketing is not merely a permutation of terms, yet is a basic matter according to a variety of specialists. There are numerous definitions that must be specifically described. "Sport marketing" implies the application of the marketing techniques already established and created in other fields. Professionals accept that conventional marketing strategies have incredibly low efficacy in the implementation of the sport field, and so this path is not today a priority and promising one. Sports promotion may be regarded as an independent area in the world of promotion.It has several variations in marketing in some fields with regard to traditional marketing standards and laws. Sport promotion is a constant quest for answers to both direct and indirect concerns of sport customers, sport firms and sport-related individuals and organizations, in a dynamic and uncertain setting, which is typical of the concept of the word ’sport.’